%I #8 Aug 09 2017 23:07:39
%S 1,8,7,6,5,4,3,2,16,15,14,13,12,11,10,9,72,71,70,69,68,67,66,65,64,63,
%T 62,61,60,59,58,57,56,55,54,53,52,51,50,49,48,47,46,45,44,43,42,41,40,
%U 39,38,37,36,35,34,33,32,31,30,29,28,27,26,25,24,23,22,21,20,19,18,17
%N a(1)=1, a(n) = 8*a(n-1) if the minimal positive integer not yet in the sequence is greater than a(n-1), else a(n) = a(n-1) - 1.
%C Also: a(1)=1, a(n) = maximal positive integer < a(n-1) not yet in the sequence, if it exists, else a(n) = 8*a(n-1).
%C Also: a(1)=1, a(n) = a(n-1) - 1, if a(n-1) - 1 > 0 and has not been encountered so far, else a(n) = 8*a(n-1).
%C A permutation of the positive integers. The sequence is self-inverse, in that a(a(n)) = n.
%F G.f.: g(x) = (x(1-2x)/(1-x) + 8x^2*f'(x^(15/7)) + (15/64)*(f'(x^(1/7)) - 8x-1)/(1-x) where f(x) = Sum_{k>=0} x^(8^k) and f'(z) = derivative of f(x) at x = z.
%F a(n) = (23*8^(r/2) - 9)/7 - n if both r and s are even, else a(n) = (78*8^((s-1)/2) - 9)/7 - n, where r = ceiling(2*log_8((7n+8)/15)) and s = ceiling(2*log_8(7n+8)/7)) - 1.
%F a(n) = (8^floor(1 + (k+1)/2) + 15*8^floor(k/2) - 9)/7 - n, where k=r if r is odd, else k=s (with respect to r and s above; formally, k = ((r+s) - (r-s)*(-1)^r)/2).
%Y For formulas concerning a general parameter p (with respect to the recurrence rule ... a(n)=p*a(n-1) ...) see A132374.
%Y For p=2 to p=10 see A132666 through A132674.
%K nonn
%O 1,2
%A _Hieronymus Fischer_, Sep 15 2007